In Vitro Anthelmintic Areca catechu Crude Aqueous Extract Against Haemonchus contortus in The Sheep - Annisa Putri Cahyani; Budi Purwo Widiarso; Supriyanto -; Wida Wahidah Mubarokah (Jurnal Sain Veteriner, 2022)
Haemonchosis is a gastrointestinal parasitic disease in sheep caused by Haemonchus contortus. The biggest economic losses due to this disease are mortality, decreased production, stunted growth, and low body weight. The existence of resistance to synthetic anthelmintics causes the development of research on alternative treatments to herbal anthelmintics to be a strategic step. This study aims to analyze the effect of Areca catechu on Haemonchus contortus in vitro so that the Lethal Concentration 50 (LC 50) can be determined. This study was divided into 9 groups. Group I was treated with 2.5% A. catechu crude aqueous extract; group II was treated with 5% of A. catechu crude aqueous extract; group III was treated with 7.5% A. catechu crude aqueous extract; group IV was treated with 10% of A. catechu crude aqueous extract; group V was treated with 12.5% A. catechu crude aqueous extract; group VI was treated with 15% A. catechu crude aqueous extract; Group VII was treated with 17.5% A. catechu crude aqueous extract, group VIII was a negative control (0.9% NaCl) and group IX was a positive control (Albendazole). The mortality of H. contortus was recorded every hour until the worm mortality was 100%. The results were then analyzed using the Reed and Muench method. Based on the in vitro test of Areca catechu crude aqueous extract against H.contortus it can cause mortality in worms with an Lethal Concentration 50 (LC 50) calculation result of 11.11%.